Cancer Related Follow-up Care among Hispanic and non-Hispanic Childhood Cancer Survivors: The Project Forward Study - Milam, Joel (Cancer, 2014)
BACKGROUND: Follow-up care is critical for childhood cancer survivors (CCS) who are at high risk for co-morbidities and late effects of cancer treatments. Understanding factors associated with maintaining follow-up care is needed, especially for Hispanic CCS who are underrepresented in previous studies. METHODS: Risk and protective factors for receiving cancer-related follow-up care were examined among 193 Los Angeles County CCS diagnosed between 2000–2007 (54% Hispanic; mean age=19.9, SD=2.8; mean age at diagnosis=12.1, SD=3.0; mean years since diagnosis=7.8, SD=2.0). Self-report surveys assessed follow-up care, insurance status, demographics, clinical factors, and psychosocial risk (e.g., depression) and protective [e.g., self-efficacy (SE)] factors. Multivariable logistic regression was used to determine factors associated with previous (in prior 2 years) and intent for future cancer-related follow-up care. RESULTS: Seventy-three percent of CCS reported a cancer follow-up visit in the prior 2 years, which was positively associated (p’s<.05) with having health insurance, White ethnicity (vs. Hispanic), younger age and greater treatment intensity. Sixty-nine percent reported intent for follow-up care in the next two years, which was positively associated (p’s<.05) with having health insurance and greater SE. CONCLUSIONS: Hispanics and older CCS are more likely to lack previous follow-up care. Because health insurance was strongly associated with both previous follow-up care and intent to seek care, recent changes in health coverage may improve follow-up among CCS. Interventions targeting improved SE may help increase intent to receive follow-up care for this population.